Role of Protein Phosphorylation in the Regulation of Cell Cycle and DNA-Related Processes in Bacteria - Garcia-Garcia, Transito; Poncet, Sandrine; Derouiche, Abderahmane; Shi, Lei; Mijakovic, Ivan; Noirot-Gros, Marie-Françoise (Frontiers in Microbiology, 2016)
In all living organisms, the phosphorylation of proteins modulates various aspects of their functionalities. In eukaryotes, protein phosphorylation plays a key role in cell signaling, gene expression, and differentiation. Protein phosphorylation is also involved in the global control of DNA replication during the cell cycle, as well as in the mechanisms that cope with stress-induced replication blocks. Similar to eukaryotes, bacteria use Hanks-type kinases and phosphatases for signal transduction, and protein phosphorylation is involved in numerous cellular processes. However, it remains unclear whether protein phosphorylation in bacteria can also regulate the activity of proteins involved in DNA-mediated processes such as DNA replication or repair. Accumulating evidence supported by functional and biochemical studies suggests that phospho-regulatory mechanisms also take place during the bacterial cell cycle. Recent phosphoproteomics and interactomics studies identified numerous phosphoproteins involved in various aspect of DNA metabolism strongly supporting the existence of such level of regulation in bacteria. Similar to eukaryotes, bacterial scaffolding-like proteins emerged as platforms for kinase activation and signaling. This review reports the current knowledge on the phosphorylation of proteins involved in the maintenance of genome integrity and the regulation of cell cycle in bacteria that reveals surprising similarities to eukaryotes.